The Garden of Learning - Amy Patton; Hyo Gyoung Jean; Roger M. Buergel; Stefan Wellgraf (editor); Busan Biennale (Busan Biennale Organizing Committee, 2012)
Biennial publication. A workshop inviting people to join the proces of exhibition making in the form of a 'Learning Council' in Busan Korea. Texts: Nam-Suk Hur, Doo-Shik Lee. Artists: Ai Weiwei, Aranberri Ibon, Seung Woo Back, Baer Jo, Basbaum Ricardo, Bayrle Thomas, Cain Ben, Carroll Mary Ellen, Choi Sunah, Diaz Gonzalo, Doujak Ines, Gowda Sheela, Guttormsgaard Guttorm, Gverovic Tina, Ham Kyungah, Hazoume Romauld, Jun Sangchul, Kapfer Franz, Kim Joohyun, Kim Sangdon, Kim Yong Ik, Krue-On Sakarin, Lee Inmi, Moe Satt, NG Royce, NHO Won Hee, Nicolai Olaf, Park Jahyun, Pei Yongmei, Poledna Mathias, Rho Jae Oon, Sekula Allan, Shen Shaomin, Stidworthy Imogen, Stollhans Jurgen, Sung Hyo-sook, Takamine Tadasu, Tellez Javier, Tomatsu Shomei, Van de ven Lidwien, Wachsmuth Simon.
English; Korean
Keywords: N4390-5098 Visual Arts- Exhibitions